2015
DOI: 10.1021/acs.inorgchem.5b00188
|View full text |Cite
|
Sign up to set email alerts
|

Mg Intercalation in Layered and Spinel Host Crystal Structures for Mg Batteries

Abstract: We investigate electrochemical properties of Mg in layered and spinel intercalation compounds from first-principles using TiS2 as a model system. Our calculations predict that Mg(x)TiS2 in both the layered and spinel crystal structures exhibits sloping voltage profiles with steps at stoichiometric compositions due to Mg-vacancy ordering. Mg ions are predicted to occupy the octahedral sites in both layered and spinel TiS2 with diffusion mediated by hops between octahedral sites that pass through adjacent tetrah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
165
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(186 citation statements)
references
References 51 publications
19
165
2
Order By: Relevance
“…Exfoliating bulk TiS 2 has been suggested as a possible method to superior performance, analogous to MoS 2 [27,161]. This intuition is supported by a theoretical study by Emly and Van der Ven [171], who looked at layered and spinel TiS 2 as a model system and compared some of the properties of Li x TiS 2 and Mg x TiS 2 . In the case of the layered polymorph, the diffusion barrier is reduced from 1.16 to 0.55 eV as the c-axis is augmented by 10% (Fig.…”
Section: Science China Materialsmentioning
confidence: 92%
“…Exfoliating bulk TiS 2 has been suggested as a possible method to superior performance, analogous to MoS 2 [27,161]. This intuition is supported by a theoretical study by Emly and Van der Ven [171], who looked at layered and spinel TiS 2 as a model system and compared some of the properties of Li x TiS 2 and Mg x TiS 2 . In the case of the layered polymorph, the diffusion barrier is reduced from 1.16 to 0.55 eV as the c-axis is augmented by 10% (Fig.…”
Section: Science China Materialsmentioning
confidence: 92%
“…Second, the honeycomb lattice of intercalant sites in P3 can result in complex sodium/vacancy ordering phenomena not seen in layered Li compounds. Bulk diffusion and interfacial ion-transfer kinetics appear to be much slower for magnesium, [277,287,288] and so some materials that are excellent for Li and Na batteries do not permit the electrochemical (de)intercalation of Mg. [8,282] The larger ionic radius of Na + (1.16 Å [283] ) compared to Li + (0.90 Å [283] ) also has other effects besides the stabilization of prismatic structures.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[8,282] The larger ionic radius of Na + (1.16 Å [283] ) compared to Li + (0.90 Å [283] ) also has other effects besides the stabilization of prismatic structures. [278,288] Relatively few studies have reported on the electrochemical (de)intercalation of elements beyond Li, Na, and Mg in layered materials. A second consequence of the larger size of Na + is that the greater discrepancy between the Na + radius and transition-metal radii results in a stronger tendency toward layering.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…As such, the Mg content of the outer shell of the active material is more likely x = 2 × 0.17 = 0.34, corresponding to the ordered composition Mg 1/3 TiS 2 where Mg occupies octahedral sites and whose existence was suggested by first-principles calculations. 31 These calculations also showed that as the unit cell increases in size with increasing Mg 2+ /e − content, the Mg 2+ preference for the octahedral site over the tetrahedral site is lessened, 31 suggesting an increased likelihood of tetrahedral occupation at high x values. Meanwhile, we note a possible parallel with lithium insertion in TiS 2 where a switchover in siting as a function of depth of intercalation occurs.…”
mentioning
confidence: 98%
“…Based on previous computational results, the octahedral site energy for Mg occupation is much lower than the tetrahedral site during the initial stages of intercalation. 31 This suggests preferred Mg insertion onto the octahedral sites during early discharge (A to C). In fact, at point C the Mg stoichiometry is likely larger than x = 0.17.…”
mentioning
confidence: 99%